2018
DOI: 10.4236/ajac.2018.93015
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Lead in Water by Linear Sweep Anodic Stripping Voltammetry (LSASV) at Unmodified Carbon Paste Electrode: Optimization of Operating Parameters

Abstract: This study presents the elaboration of a simple and cheap electrode made by carbon paste introduced into a cavity of electrode body, and used for the lead traces determination in tap water. A potentiostatic pre-electrolysis at constant voltage enables the reduction of the lead (Pb 2+ ) and the accumulation of the metallic lead at and into the carbon paste; the reoxidation of the Pb (Linear sweep voltammetry) leads to the anodic striping peak. The effect of the main operating parameters on the shape of the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…coupled plasma-mass spectrometry (ICP-MS) [29,30], UV-VIS [31], HPLC-inductively coupled plasma-mass spectrometry (HPLC -ICP -MS) [32], electrophoresis(EP) [33], Anodic striping voltammetry (AVS) and inductively coupled plasma-mass spectrometry (ICP-MS) was used for heavy metal determination in different matrix [34,35]. Arida et al showed that the assessment of heavy and toxic metals in the blood and hair by modern analytical techniques in review paper.…”
mentioning
confidence: 99%
“…coupled plasma-mass spectrometry (ICP-MS) [29,30], UV-VIS [31], HPLC-inductively coupled plasma-mass spectrometry (HPLC -ICP -MS) [32], electrophoresis(EP) [33], Anodic striping voltammetry (AVS) and inductively coupled plasma-mass spectrometry (ICP-MS) was used for heavy metal determination in different matrix [34,35]. Arida et al showed that the assessment of heavy and toxic metals in the blood and hair by modern analytical techniques in review paper.…”
mentioning
confidence: 99%
“…As described before, the lower the potential applied, the more the cathodic current is needed to increase Pb +2 ion reduction, thus increasing its electrodeposition on the electrode surface, which leads to an increase in the oxidation process of Pb 0 to Pb +2. [ 64 ] The current responses for 100 s and 150 s were similar; however, a shorter time was preferred for fast detection. The observed signal decrease with high deposition time and potential was caused by the accumulation and competition of Pb 2+ ions, which hindered them from reaching the electrode surface.…”
Section: Resultsmentioning
confidence: 99%
“…surfactant modified zeolite carbon paste electrode). 7,81,82 Od teških metala, uz pomoć CPE primjenjujući elektroanalitičke tehnike, osim žive 21,83 i bakra, [84][85][86] različiti autori su opisali primjenu CPE za određivanje olova, [86][87][88][89] kadmija, 86,88,90,91 cinka, 86,88 talija, [92][93][94] kositra, 91 bizmuta, 95,96 antimona 97 i dr. Potenciometrijom se uz CPE mogu odrediti maseni udjeli aluminija niži i od 10 −9 . 98 Sve gore navedene elektrode od ugljikove paste pokazale su se kao dovoljno osjetljive, selektivne i pouzdane u određivanju niskih koncentracija ispitivanih analita.…”
Section: Literaturni Pregled Upotrebe Modificiranih Cpe U Potenciomet...unclassified